Sovereignty and the Limits of Indigenous Rights in West Papua - Webb-Gannon, Camellia (Waka Kuaka, 2022)
This article examines an apparent political paradox facing Indigenous West Papuans as they grapple with the issue of how to represent themselves to the outside world in order to ensure their survival and protect their dignity: that is, they must simultaneously present as one body and as many—as a unified nation deprived of and legitimately entitled to a state, and as a multiplicity of diverse Indigenous peoples requiring the protection of Indigenous rights to safeguard their cultures. Echoing the perspectives of prominent West Papuan rights advocates, this article argues that Indigenous rights alone are insufficiently comprehensive and powerful in their ability to protect the lives, livelihoods and cultures of West Papuans. To be effective, Indigenous rights for West Papuans must follow the actualisation of sovereignty—specifically, the Westphalian-influenced notion of sovereignty implied in the right to self-determination enshrined in the 1966 United Nations International Covenant on Civil and Political Rights and International Covenant on Economic, Social and Cultural Rights. West Papuans must first be recognised as a singular body politic, a pan-Papuan nation with an attendant right to statehood, before they can live safely and fully as Indigenous peoples.